(untitled) (Revista de Investigaciones Universidad del Quindío, 2011)
The Neem tree (Azadirachta indica A. Juss), which gives a large amount of chemicals, has problems in sexual reproduction, with little viable seed. The aim of this study was to induce callus formation processes and indirect organogenesis from A. indica leaf discs and perform phytochemical screening for the presence of secondary metabolites in callus obtained. Leaves of A. indica were taken and classified according to their position in the leaf: apical, middle, baseline; for the disinfection phase NaOCl 3% for 5 and 10 min of immersion was evaluated. For the induction phase, two concentrations of auxin picloram (1 and 2.0 mg/L) were evaluated. The best index of disinfection, with less damage in the tissue explant, was achieved by immersion in NaOCl for 10 min, for induction, both concentrations showed a generation of callus. The calluses obtained were transferred to different concentrations of BAP (0.5, 1.0, 1.5 and 2.0 mg/L) and subcultured for 4 months, in which most had rust. Furthermore, none of the concentrations (BAP) had presence of organogenic structures. The phytochemical screening of both calluses and fresh leaves gave positive results for alkaloids, flavonoids, sesquiterpene lactone, steroids and / or Triterpenes, Coumarins volatile and Cardiotonic.